Effects of Different Combination of Water Quality Parameters on the Survival and Growth of Juvenile Barbonymus schwanenfeldii, Leptobarbus hoevenii and Oreochromis niloticus - Danial Nakhaie, bin Mohd Souhkri (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Change in water quality parameters give impact to the fish in their natural environment. In order to determine such effects, survival and growth performance of juveniles Barbonymus schwanenfeldii, Leptobarbus hoevenii and Oreochromis niloticus were tested in laboratory with different combinations of water quality parameters. The combinations were pH and temperature, total suspended solids and temperature, dissolved oxygen and temperature, and total suspended solids and pH. When tested with combination of pH and temperature, it was shown that the 100% survival rate was at pH 7.0 temperature 27°C. For combination of total suspended solids and temperature, 100% survival was observed at 0 mg/L total suspended solids in both 27°C and 29°C. Combination of dissolved oxygen and temperature showed 100% survival at 7.0 mg/L dissolved oxygen in both 27°C and 29 °C. The survival and growth was reduced as the dissolved oxygen concentration decreased. In all three experiments that involved different temperatures, the same trends were observed but the effect was enhanced. When tested with combination of total suspended solids and pH, 0 mg/L total suspended solids pH 7.0 showed the highest survival rate and growth of juveniles. In the experiment it was shown that increment of total suspended solids and decrease in pH, decrease the survival and growth of juveniles. All of the result showed that change in one water quality parameter can give negative impact to the juveniles, but combinations of different water quality parameters will multiply the effect. Also, the exotic species show greater hardiness compared to native species.